The Contribution of NGO in Public Diplomacy: A Case Study of the Singapore Institute of International Affairs in Resolving the Transboundary Haze Pollution Issue between Singapore-Indonesia (2012-2016) - Angela, Jessica; Hikam, Muhammad A.S. (President University, 2019)
In 2013, Southeast Asian countries have to face a disastrous haze pollution coming from Indonesia. Transboundary Haze Pollution (THP) is a deadly occurrences that repeats annually. As a result, Indonesia’s neighboring countries must encounter disadvantageous consequences. One of the countries gradually affected is Singapore, since they have been through haze pollution since the late 1980’s. Various attempts have been made by Singapore to mitigate the disaster. Since bilateral and regional efforts do not give any solution, Singapore then implies public diplomacy efforts. The practices of these public diplomacy could be seen from the involvement of one of the nation’s influential NGOs, the Singapore Institute of International Affairs (SIIA). As a result, they are able to pressure Indonesia in applying a more comprehensive map for haze tracker. Therefore, this study expects to invite readers’ interest in the issue of NGO, precisely in International Relations and Public Diplomacy. This study will specifically discuss the practice of SIIA as public diplomacy efforts to resolve the THP issue from 2012 until 2016.